Facing the Indigenous ‘Other’: Culturally Responsive Research and Pedagogy in Music Education - Locke, Terry; Prentice, Lauren (The Australian Journal of Indigenous Education, 2016)
This narrative article is based on an analysis of 61 documents, mostly articles, of which 37 were peer-reviewed, including research studies, reviews, conceptual research and narratives of practice. Review findings are reported with specific reference to the Australian and New Zealand contexts in relation to the following topic categories: the presence of indigenous music in the curriculums of selected ‘new world’ countries, teacher education in indigenous performing arts, questions of curriculum design and programming, resource selection, activity design, and school and community relationships. Certain key themes emerged across these topics: the need for a greater emphasis on more culturally nuanced music teacher education in relation to indigenous musics; the critical importance of teaching indigenous music/arts contexts; song ownership; and the need for music educators and researchers to develop a critical stance towards their subject and discipline.